Association between hypertension in adolescents and the health risk factors of their parents: an epidemiological family study - Christofaro, Diego Giulliano Destro [UNESP]; Mesas, Arthur E.; Ritti Dias, Raphael M.; Fernandes, Rômulo A. [UNESP]; Saraiva, Bruna T.C. [UNESP]; Palma, Mariana R. [UNESP]; Silva, Diego A.S.; de Andrade, Selma M. (Elsevier, 2018)
Hypertension in adolescence may be a predictor of cardiovascular problems in adulthood. Therefore, verification of the factors associated with this condition in adolescence is important. The aim of this study was to analyze the relationship between hypertension in adolescents with hypertension and the sociodemographic characteristics and lifestyle of their parents. This study was conducted on 1231 adolescents, 1202 mothers, and 871 fathers. The blood pressure of the adolescents was measured with an oscillometric device. Details of parental hypertension, sociodemographic characteristics, and lifestyle were obtained by self-report. The prevalence of hypertension was higher among adolescents with older fathers and older mothers, with both parents reporting hypertension and with mothers who were overweight. In multivariable analysis, adolescents with older mothers (OR = 2.36; 95% confidence interval [CI] = 1.12–4.98), hypertensive mothers (OR = 2.22 [95% CI = 1.26–3.89]), and hypertensive fathers (OR = 1.70 [95% CI = 1.03–2.81]) were more likely to have hypertension. In the analysis that considered clusters of health risk factors, higher risks of hypertension were observed in adolescents whose mothers had four or more aggregated risk factors (OR = 2.53 [95% CI = 1.11–5.74]). In conclusion, there was a relationship between hypertension in adolescents and hypertension in their parents. However, an association between hypertension in adolescents and parental age and clusters of health risk factors was only observed for their mothers.
Keywords: Blood pressure; fathers and mothers; youth